The effect of climate change on the radial growth of Pinus sylvestris l. and Quercus robur l. in the stands of Kharkiv green zone - Koval , I. M.; Bräuning , A. (Man and Environment. Issues of Neoecology, 2024)
Purpose. To identify the characteristics of the reaction of the radial growth of Scots pine (Pinus Sylvestris L.) and Scots oak (Quercus robur L.) to climate change in the forest-steppe zone of Ukraine. Methods. Dendrochronological, dendroclimatological, and statistical methods are applied. COFECHA and ARSTAN programs were used. Results. The study was conducted in 100-year-old stands of English oak and Scots pine in the Southern Forestry (Left-bank Forest-steppe). The reaction of the radial growth of trees to climate changes was compared for 1960-1987 and 1988-2016. For the dendroclimatic analysis, the de Martonne hydrothermal indices, the Selyaninov hydrothermal coefficient, the forest aridity index, and the O1 hydrothermal coefficient were used. Relative humidity indicators, which are derived from temperature and precipitation, were also used. It was found that in the second period, the sensitivity of the reaction of the radial growth of trees to climate variations increased, which indicates a certain weakening of the stands due to the increase in temperature. Dendroclimatic analysis of Pinus sylvestris L. and Quercus robur L. showed that when comparing the response of the radial growth of trees to climate variations in 1960-1987 and 1988-2016, the condition of both pine and oak weakened, as evidenced by an increase in significant coefficients correlations between growth indices and climatic factors. Conclusions. Pine was found to be more sensitive to climate change compared to oak. At the same time, these species of these trees at this stage were able to adapt to climate change, as evidenced by tree-ring chronologies, which show stable growth during 2010-2016.